Relationship between health literacy and COVID-19 preventive behaviors in new normal era among working-age people in the Bangkok Metropolitan and its suburbs - Adamchareon, Benjamaporn; Iemsawasdikul, Warinee (Thai Journal of Nursing, 2022)
The objective of this descriptive research was to study the relationship between health literacy and COVID-19 preventive behaviors in the “ new normal ” era among working-age people in the Bangkok Metropolitan and its suburbs. The sample comprised 421 people aged 18-59 years who lived in the Bangkok Metropolitan and its suburbs. They were selected by convenience sampling. The research tool was a Google form questionnaire with 3 parts; 1) personal data, 2) health literacy about COVID-19, and 3) COVID-19 preventive behaviors. Data were collected by sharing OR code and analyzed by descriptive statistics, Phi Correlation and Odds Ratio. The results were as follows. 1) Overall and all subsets of health literacy about COVID-19 were at the high level. 2) Overall and 1 subset of COVID-19 prevention behaviors in the new normal era were at the high level, and two subsets were at the highest level. 3) Overall and subsets of health literacy were significantly correlated with overall and subsets of COVID-19 preventive behaviors in the new normal era at the lowest, low, and moderate levels (p< .05).